A decade of RAD51C and RAD51D germline variants in cancer. Issue 3 (30th December 2021) - Boni, Jacopo; Idani, Aida; Roca, Carla; Feliubadaló, Lidia; Tomiak, Eva; Weber, Evan; Foulkes, William D.; Orthwein, Alexandre; El Haffaf, Zaki; Lazaro, Conxi; Rivera, Barbara
Abstract: Defects in DNA repair genes have been extensively associated with cancer susceptibility. Germline pathogenic variants (GPV) in genes involved in homologous recombination repair pathways predispose to cancers arising mainly in the breast and ovary, but also other tissues. The RAD51 paralogs RAD51C and RAD51D were included in this group 10 years ago when germline variants were associated with non‐ BRCA1/2 familial ovarian cancer. Here, we have reviewed the landscape of RAD51C and RAD51D germline variants in cancer reported in the literature during the last decade, integrating this list with variants identified by in‐house patient screening. A comprehensive catalog of 341 variants that have been classified applying ACMG/AMP criteria has been generated pinpointing the existence of recurrent variants in both genes. Recurrent variants have been extensively discussed compiling data on population frequencies and functional characterization if available, highlighting variants that have not been fully characterized yet to properly establish their pathogenicity. Finally, we have complemented this data with relevant information regarding the conservation of mutated residues among RAD51 paralogs and modeling of putative hotspot areas, which contributes to generating an exhaustive update on these two cancer predisposition genes. Abstract : Germline Pathogenic Variants, including likely pathogenic and pathogenic variants, reported in the last decade in RAD51C and RAD51D.